Application of Graphene in Surface-Enhanced Raman Spectroscopy - Jie Chang; Xiao Zhi; Amin Zhang (Nano Biomedicine and Engineering, 2017)
Since the two-dimension structural graphene was discovered in 2004, the researches involved in graphene have and will continue to develop actively because of the excellent properties of graphene. Raman spectroscopy is a quick and precise characterization technique for investigating material properties in material science. Meanwhile, surface-enhanced Raman scattering (SERS) consumingly impacts on surface science owing to its extremely high sensitivity at single molecule level. However, SERS has not been an expected powerful analytical technique due to a variety of technical limitations. Here we briefly review some critical progresses in the development of surface-enhanced Raman scattering (SERS) and various applications of graphene in SERS in recent years.